Formulasi Sediaan Sabun Transparan Dari Ekstrak Biji Pinang (Arecha catecchu L.) Sebagai Antibakteri - Huda, Nurul; Anglia, Rima; Barus, Rakhmad; Maluntoh, Adriana Corneli (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Research has been carried out on the formulation of Transparent Soap Preparations from Areca Seed Extract (Areca catechu L.). The purpose of the study was to find out the best formula for transparent soap preparations for areca nut extract. The type of this research is descriptive method with laboratory experimental approaches. The research was carried out at the Laboratory of the Faculty of Health Sciences, Jayapura University of Science and Technology. The population used in this study was Betel Nuts in the Yatu Raharja Village (Arso x) District, District Arso, Keerom Regency. The number of samples in the study was 3 kg. The basic ingredients are taken from betel nut and the active ingredients are taken from maceration for three times twenty four hours using 70% ethanol as solvent. The formulation was carried out with variations of formulas I, II, and III with the concentration of sucrose as the formation of the soap transparency structure, namely 5%, 10%, 15%. To get the best formula, an evaluation of the preparation was carried out including organoleptic testing, pH testing, foam stability testing, water content testing, physical stability testing, and irritation testing. The results showed that the best formula was formula III with a sucrose concentration of 15% with organoleptic evaluation test results showing a transparent solid form, distinctive grape fruit aroma, orange color, pH 10.5, foam stability 9.5cm, water content 28%, stable and non-irritating.